Deposition and Characterization of Dielectric Distributed Bragg Reflectors - Lapp, Michael (My University, 2016)
The Vertical Cavity Surface Emitting Laser (VCSEL) is a laser well suited for data centre applications due to its low cost, high speeds, good fiber coupling, and low threshold current The current standard wavelength for short-haul is 850 nm, however switching to 980 nm can improve transmission distance in optical fiber by lowering absorption and chromatic dispersion. To improve the performance of VCSELs, mirrors with less optical loss can be used. VCSELs require mirrors with > 99 % reflectance, and Distributed Bragg Reflectors (DBRs) are used to achieve this. Today, epitaxially-grown semiconductor DBRs are used, however these have low refractive index contrast, scattering from dopants, and free-carrier absorption. These DBRs can be replaced by dielectric ones which can offer higher refractive index contrast and less absorption. These properties can increase optical confinement in the gain region and decrease losses in the mirrors leading to VCSELs with more output power and lower threshold currents. DBRs using dielectric materials to reflect 980 nm light above 99 % are therefore of key interest. In this work DBRs with SiO2/TiO2 layers as well as SiO2/a-Si were deposited by sputtering. Mirrors were fabricated with 2, 4, 6, and 8 pairs for each set of materials. A measurement setup was built to measure reflectances above 99 % with ±0.03 % accuracy to evaluate the mirrors. DBRs of SiO2/TiO2 were found to achieve above 99 % reflectance for 6 and 8 pairs with measured reflectances of 99.42 ± 0.03 % and 99.80 ± 0.03 % respectively with negligible extinction coefficient. SiO2/a-Si DBRs achieved over 99 % reflectance for 4, 6, and 8 pairs with measured reflectances of 99.36 ± 0.03 %, 99.02 ± 0.03 %, and 99.17 ± 0.03 % respectively with extinction coefficient for a-Si between 0.0010 and 0.0015 at 980 nm All DBRs agreed well with simulated results. SiO2/TiO2 mirrors were found to have more reliable deposition and achieved higher reflectances. SiO2/a-Si DBRs on the other hand were found to have less reliable deposition and their reflectance saturated above 6 pairs due to the higher extinction coefficient in a-Si, indicating little to no light is transmitted out of these DBRs, limiting their usefulness for VCSELs. A 6-pair SiO2/TiO2 DBR appears very promising to use in VCSELs due to the superior reliability of the materials and increased output power from a slightly lower reflectance than the 8-pair mirror.
Keywords: Informations- och kommunikationsteknik; Nanovetenskap och nanoteknik; Fotonik; Nanoteknik; Information & Communication Technology; Nanoscience & Nanotechnology; Photonics; Nano Technology